A hard carbon material and its preparation method and application

By using hard carbon materials in the negative electrode materials of lithium-ion batteries, amorphous carbon cladding is formed through reflux and high-temperature sintering, the problem of insufficient specific capacity and first efficiency of the negative electrode materials of lithium-ion batteries is solved, and efficient electrochemical performance is achieved and Economical preparation method.

CN115483395BActive Publication Date: 2025-01-03GANZHOU LITAN NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211367611.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-03
Publication Date
2025-01-03
Estimated Expiration
2042-11-03

AI Technical Summary

Technical Problem

The specific capacity and first efficiency of the negative electrode materials of existing lithium-ion batteries are insufficient, especially the theoretical specific capacity of the graphite negative electrode. Lattice defects in the preparation process of non-graphite carbon negative electrode materials affect the electrochemical performance.

Method used

Using hard carbon material, by mixing the first carbon source and organic amine for reflux and low-temperature sintering, the d002 surface layer spacing of the carbonaceous material is increased, and then high-temperature sintering with the second carbon source to form an amorphous carbon cladding layer, which improves the The carbon layer spacing of the material and reduces surface defects.

Benefits of technology

It achieves high specific capacity and high first efficiency of hard carbon materials, which is suitable as a negative electrode material for secondary battery, and has both economical preparation costs and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115483395B_ABST
    Figure CN115483395B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of secondary batteries, and specifically relates to a hard carbon material and a preparation method and application thereof. The hard carbon material provided by the present invention comprises a carbonaceous material and a carbon coating layer on the surface of the carbonaceous material; the d002 interlayer spacing of the hard carbon material is 0.36 to 0.42 nm; and the carbon coating layer is amorphous carbon. In the present invention, the hard carbon material has a large carbon interlayer spacing, which is beneficial to the deintercalation of ions during the charging and discharging process, thereby increasing the gram capacity of the hard carbon material; the present invention coats the carbon layer on the surface of the carbonaceous material to reduce the defects on the surface of the carbonaceous material, thereby increasing the reversible capacity of the hard carbon material and further increasing the initial efficiency of the hard carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a hard carbon material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in the fields of 3C consumer batteries, power batteries and energy storage batteries due to their advantages such as good stability, high energy density and no memory effect. The negative electrode materials of commercial lithium-ion batteries currently include graphite materials and non-graphite carbon materials. Among them, the theoretical specific capacity of the graphite negative electrode is only 372mAh / g, which makes it difficult to effectively improve the high-rate continuous charge and discharge capacity and low-temperature performance. During the preparation process of non-graphite carbon negative electrode materials, a large number of lattice defects will be generated in the internal structure. Although these lattice defects are conducive to improving the specific capacity of non-graphite carbon negative electrode materials, these lattice defects will also lead to a decrease in the first efficiency of non-graphite carbon negative electrode materials, affecting the electrochemical properties of non-graphite carbon negative electrode materials. Therefore, the development of a lithium battery negative electrode material with both high specific capacity and high first efficiency is an important direction of current research. Summary of the invention

[0003] In view of this, the present invention provides a hard carbon material and a preparation method and application thereof. The hard carbon material provided by the present invention has both high specific capacity and first efficiency and good electrochemical performance.

[0004] In order to solve the above technical problems, the present invention provides a hard carbon material, comprising a carbonaceous material and a carbon coating layer on the surface of the carbonaceous material;

[0005] The d002 interlayer spacing of the hard carbon material is 0.36-0.42 nm; and the carbon coating layer is amorphous carbon.

[0006] Preferably, the thickness of the carbon coating layer is 30 to 1200 nm.

[0007] Preferably, the median particle size D50 of the hard carbon material is 2 to 18 μm.

[0008] Preferably, the specific surface area of ​​the hard carbon material is 1 to 15 m 2 / g.

[0009] The present invention also provides a method for preparing the hard carbon material described in the above technical solution, comprising the following steps:

[0010] The first carbon source and the organic amine are mixed and then refluxed and low-temperature sintered in sequence to obtain a carbonaceous material; the reflux temperature is 75 to 120° C., the reflux time is 2 to 5 hours; the low-temperature sintering temperature is 250 to 600° C.;

[0011] The carbonaceous material and the second carbon source are mixed and then sintered at high temperature to obtain the hard carbon material; the temperature of the high temperature sintering is 700-1500°C.

[0012] Preferably, the low-temperature sintering time is 1 to 6 hours.

[0013] Preferably, the organic amine includes one or more of ethylenediamine, triethylamine, triethanolamine and hexamethylenetetramine;

[0014] The first carbon source includes one or more of natural biomass materials, resin materials, asphalt and plant extracts;

[0015] The mass ratio of the first carbon source to the organic amine is 1:0.5-1.2.

[0016] Preferably, the second carbon source includes a solid carbon source, a liquid carbon source or a gaseous carbon source;

[0017] The mass ratio of the carbonaceous material to the second carbon source is 1:0.02-0.2.

[0018] Preferably, the solid carbon source comprises one or more of polydopamine, polyvinyl pyrrolidone, polystyrene, asphalt, glucose and sucrose;

[0019] The liquid carbon source is obtained by dissolving a solid carbon source in a solvent, and the solvent includes one or more of water, ethanol, toluene, ethyl acetate and n-heptane;

[0020] The gaseous carbon source includes one or more of methane, ethane, ethylene, acetylene, propane, propylene, acetone, butane, butene, pentane and hexane.

[0021] The present invention also provides the use of the hard carbon material described in the above technical solution or the hard carbon material prepared by the preparation method described in the above technical solution as a negative electrode material for a secondary battery.

[0022] The present invention provides a hard carbon material, comprising a carbonaceous material and a carbon coating layer on the surface of the carbonaceous material; the d002 interlayer spacing of the hard carbon material is 0.36-0.42nm; the carbon coating layer is amorphous carbon. In the present invention, the hard carbon material has a large carbon interlayer spacing, which is conducive to the deintercalation of ions during the charge and discharge process, thereby increasing the gram capacity of the hard carbon material; the present invention coats the surface of the carbonaceous material with an amorphous carbon layer to reduce the concave-convex defects on the surface of the carbonaceous material, thereby increasing the efficiency of the hard carbon material and further increasing the gram capacity of the hard carbon material.

[0023] The present invention also provides a method for preparing the hard carbon material described in the above technical solution, comprising the following steps: mixing a first carbon source and an organic amine, and then refluxing and low-temperature sintering in sequence to obtain a carbonaceous material; the reflux temperature is 75 to 120°C, and the reflux time is 2 to 5 hours; the low-temperature sintering temperature is 250 to 600°C; mixing the carbonaceous material and a second carbon source, and then sintering at high temperature to obtain the hard carbon material; the high-temperature sintering temperature is 700 to 1500°C. In the present invention, refluxing the first carbon source and the organic amine increases the d002 interlayer spacing of the carbonaceous material, and then coating the carbon layer on the surface of the carbonaceous material by high-temperature sintering to reduce the defects on the surface of the carbonaceous material. The hard carbon material obtained according to the preparation method provided by the present invention has both high gram capacity and first efficiency. The raw materials used in the preparation method provided by the present invention are cheap, the process is simple, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the XRD spectrum of the hard carbon material prepared in Example 1;

[0025] Figure 2 This is the SEM spectrum of the hard carbon material prepared in Example 1;

[0026] Figure 3 This is the first charge and discharge curve of a button cell prepared using the hard carbon material prepared in Example 1 as the negative electrode active material. DETAILED DESCRIPTION

[0027] The invention provides a hard carbon material, comprising a carbonaceous material and a carbon coating layer on the surface of the carbonaceous material.

[0028] In the present invention, the d002 interlayer spacing of the hard carbon material is 0.36-0.42 nm, preferably 0.37-0.382 nm. In the present invention, the carbon coating layer is amorphous carbon; the thickness of the carbon coating layer is preferably 30-1200 nm, more preferably 50-500 nm.

[0029] In the present invention, the hard carbon material is preferably a particle, and the median particle size D50 of the hard carbon material is preferably 2 to 18 μm, more preferably 5 to 15 μm. In the present invention, the specific surface area of ​​the hard carbon material is preferably 1 to 15 m 2 / g, more preferably 3 to 12 m 2 / g.

[0030] The present invention also provides a method for preparing the hard carbon material described in the above technical solution, comprising the following steps:

[0031] The first carbon source and the organic amine are mixed and then refluxed and low-temperature sintered in sequence to obtain a carbonaceous material; the reflux temperature is 75 to 120° C., the reflux time is 2 to 5 hours; the low-temperature sintering temperature is 250 to 600° C.;

[0032] The carbonaceous material and the second carbon source are mixed and then sintered at high temperature to obtain the hard carbon material; the temperature of the high temperature sintering is 700-1500°C.

[0033] The method for preparing the hard carbon material comprises the following steps:

[0034] The present invention mixes the first carbon source and the organic amine, and then refluxes and sinters at a low temperature in sequence to obtain a carbonaceous material. In the present invention, the first carbon source preferably includes one or more of natural biomass materials, resin materials, asphalt and plant extracts, and more preferably biomass materials, resin materials or plant extracts. In the present invention, the biomass material preferably includes one or more of apricot shells, walnut shells, rice shells, peanut shells, pistachio shells, coconut shells, bamboo, hazelnuts and straw, and more preferably apricot shells or straw. In the present invention, when the biomass material includes two or more of the above-mentioned specific substances, the present invention has no special limitation on the ratio of the specific substances, and any ratio can be used.

[0035] In the present invention, the resin material preferably includes one or more of phenolic resin, epoxy resin, furfural resin and acrylic resin, and more preferably phenolic resin or acrylic resin. In the present invention, when the resin material includes two or more of the above-mentioned specific substances, the present invention has no special limitation on the ratio of the specific substances, and any ratio can be used.

[0036] In the present invention, the asphalt preferably includes one or more of petroleum asphalt, coal asphalt and natural asphalt, and petroleum asphalt is more preferred. In the present invention, when the asphalt includes two or more of the above-mentioned specific substances, the present invention has no special limitation on the ratio of the specific substances, and any ratio can be used.

[0037] In the present invention, the plant extract preferably includes one or more of starch, sucrose, glucose, cellulose, maltose and natural rubber, and more preferably starch or cellulose. In the present invention, when the plant extract includes two or more of the above-mentioned specific substances, the present invention has no special limitation on the ratio of the specific substances, and any ratio can be used.

[0038] In the present invention, the organic amine preferably includes one or more of ethylenediamine, triethylamine, triethanolamine and hexamethylenetetramine, and more preferably triethylamine, triethanolamine or hexamethylenetetramine. In the present invention, when the organic amine includes two or more of the above-mentioned specific substances, the present invention has no special limitation on the ratio of the specific substances, and any ratio can be used.

[0039] In the present invention, the mass ratio of the first carbon source to the organic amine is preferably 1:0.5-1.2, more preferably 1:0.6-0.95.

[0040] The present invention has no special requirements for the mixing, as long as it can be mixed evenly. In the present invention, the reflux temperature is 75-120°C, preferably 90-100°C; the reflux time is 2-5h, preferably 2-3h. The present invention mixes the first carbon source and the organic amine and then refluxes to etch, which increases the d002 interlayer spacing of the carbonaceous material, thereby increasing the internal structural voids of the carbonaceous material and improving the gram capacity of the hard carbon material.

[0041] In the present invention, after the reflux, it is preferred that the process further includes: cooling the system after the reflux and filtering it, and drying the solid obtained by filtration. In the present invention, the temperature after the cooling is preferably 20 to 35°C, more preferably 25 to 30°C. The present invention has no special requirements for the cooling method, as long as the required temperature can be reached. The present invention has no special limitations on the filtration, and conventional filtration methods in the art can be used. In the present invention, the drying temperature is preferably 80 to 125°C, more preferably 90 to 110°C; the drying time is preferably 2 to 8h, more preferably 3 to 6h.

[0042] In the present invention, the temperature of the low-temperature sintering is 250-600° C., preferably 300-400° C.; the time of the low-temperature sintering is preferably 1-6 hours, more preferably 2-4 hours.

[0043] In the present invention, the low-temperature sintering is preferably performed in a protective atmosphere, and the protective atmosphere preferably includes nitrogen or argon, more preferably nitrogen.

[0044] In the present invention, after the low-temperature sintering, the process preferably further comprises: grinding the product after the low-temperature sintering and then washing it. In the present invention, before the grinding, the process preferably further comprises: cooling the product after the low-temperature sintering; the temperature after the cooling is preferably 20 to 35°C, more preferably 25 to 30°C. In the present invention, the median particle size D50 of the product after the grinding is preferably 2 to 18 μm, more preferably 4 to 12 μm. The present invention has no special requirements for the grinding, as long as the desired particle size can be achieved.

[0045] In the present invention, the washing preferably includes one or more of water washing, alkali washing and acid washing, more preferably water washing, alkali washing followed by water washing or acid washing followed by water washing. In the present invention, the pH value of the alkaline solution for alkali washing is preferably greater than or equal to 12, more preferably 12 to 13; the pH value of the acid solution for acid washing is preferably less than or equal to 2, more preferably 1 to 2. The present invention has no special requirements for the types of the alkaline solution and the acid solution, as long as they can meet the above-defined pH value range.

[0046] The present invention can remove impurities in the product obtained by low-temperature sintering through purification, thereby improving the purity of the carbonaceous material and thus improving the gram capacity of the hard carbon material.

[0047] In the present invention, after washing, the washing process preferably further comprises: drying the washed product, the drying temperature is preferably 80 to 130° C., more preferably 90 to 120° C.; the drying time is preferably 2 to 8 hours, more preferably 2 to 5 hours.

[0048] After obtaining the carbonaceous material, the present invention mixes the carbonaceous material and a second carbon source and then performs high-temperature sintering to obtain the hard carbon material. In the present invention, the second carbon source includes one or more of a solid carbon source, a liquid carbon source and a gaseous carbon source, more preferably a solid carbon source, a liquid carbon source or a solid carbon source and a gaseous carbon source. In the present invention, the solid carbon source preferably includes one or more of polydopamine, polyvinyl pyrrolidone, polystyrene, asphalt, glucose and sucrose, more preferably glucose or polyvinyl pyrrolidone. In the present invention, when the solid carbon source includes two or more of the above-mentioned specific substances, the present invention has no special requirements for the ratio of the specific substances, and any ratio can be used.

[0049] In the present invention, the liquid carbon source is preferably obtained by dissolving a solid carbon source in a solvent; the solvent preferably includes one or more of water, ethanol, toluene, ethyl acetate and n-heptane, more preferably water or ethanol. In the present invention, the mass concentration of the liquid carbon source is preferably 5 to 50%, more preferably 5 to 25%. The present invention has no special requirements for the dissolution, as long as it can be mixed evenly.

[0050] In the present invention, the gaseous carbon source preferably includes one or more of methane, ethane, ethylene, acetylene, propane, propylene, acetone, butane, butene, pentane and hexane, and more preferably methane, ethylene or acetylene. In the present invention, when the gaseous carbon source includes two or more of the above-mentioned specific substances, the present invention has no special requirements for the ratio of the specific substances, and any ratio can be used. In the present invention, when acetone, pentane and hexane are selected as the gaseous carbon source, it is preferred to gasify the acetone, pentane and hexane first.

[0051] In the present invention, the mass ratio of the carbonaceous material to the second carbon source is preferably 1:0.02 to 1.5, more preferably 1:0.05 to 0.2.

[0052] In the present invention, when the second carbon source is a solid carbon source, the present invention has no special requirements for the mixing, as long as it can be mixed evenly.

[0053] In the present invention, when the second carbon source is a liquid carbon source, the present invention preferably spray-dries the carbonaceous material and the liquid carbon source after mixing. The present invention has no special requirements for the spray drying, as long as the solvent in the product can be removed.

[0054] In the present invention, when the second carbon source is a gas-phase carbon source, the mixing is preferably vapor deposition. The present invention has no special requirements for the vapor deposition, as long as the gas-phase carbon source can be evenly distributed on the surface of the carbonaceous material.

[0055] In the present invention, the high temperature sintering temperature is 700-1500°C, preferably 1000-1300°C; the high temperature sintering time is preferably 1-10h, more preferably 2-8h. In the present invention, the second carbon source is sintered and cracked into amorphous carbon coated on the surface of the carbonaceous material.

[0056] In the present invention, the number of high-temperature sintering is preferably at least once, more preferably 2 to 3 times. In the present invention, after each high-temperature sintering, the product of high-temperature sintering is preferably cooled and screened. In the present invention, the temperature after cooling is preferably 20 to 35°C, more preferably 25 to 30°C. The present invention has no special requirements for the screening, and conventional methods in the art can be used. The present invention can evenly coat the amorphous carbon on the surface of the carbonaceous material through high-temperature sintering, reduce the defects on the surface of the carbonaceous material, and thus improve the primary efficiency and gram capacity of the hard carbon material.

[0057] In the present invention, the high temperature sintering is preferably carried out under a protective atmosphere, and the protective atmosphere preferably includes nitrogen, helium, neon or argon, more preferably nitrogen or argon.

[0058] The present invention also provides the use of the hard carbon material described in the above technical solution or the hard carbon material prepared by the preparation method described in the above technical solution as a negative electrode material for a secondary battery. In the present invention, the hard carbon material is used as an active substance of the negative electrode material.

[0059] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0060] Example 1

[0061] 5 kg of apricot shells and 3 kg of triethylamine were mixed and refluxed at 90° C. for 3 h, cooled to 30° C. and filtered, and the filtered solid was dried at 90° C. for 2 h; the dried product was sintered at 400° C. for 4 h in a nitrogen atmosphere, cooled to 30° C., ground and sieved to a D50 of 5±1 μm, acid-washed with a hydrochloric acid solution with a pH value of 2, washed with water until neutral, and dried at 100° C. for 3 h to obtain a carbonaceous material;

[0062] The carbonaceous material and glucose (the mass ratio of carbonaceous material to glucose is 1:0.05) are solid-phase mixed and sintered at 1250°C for 1 hour. After cooling to 30°C, the high-temperature sintered product is solid-phase mixed with glucose (the mass ratio of carbonaceous material to glucose is 100:5) again and sintered at 1250°C for 1 hour. After cooling to 30°C, the product is sieved to obtain a median particle size D50 of 4.9 μm.

[0063] Example 2

[0064] 3 kg of starch and 2.1 kg of triethanolamine were mixed and refluxed at 100° C. for 2 h, cooled to 30° C. and filtered, and the filtered solid was dried at 100° C. for 2.5 h; the dried product was sintered at 400° C. for 4 h in a nitrogen atmosphere, cooled to 30° C., ground and sieved to a D50 of 8±1 μm, washed with an ammonia solution with a pH value of 12, and then washed with water until neutral, and dried at 95° C. for 2.5 h to obtain a carbonaceous material;

[0065] The carbonaceous material and polyvinyl pyrrolidone (the mass ratio of carbonaceous material to polyvinyl pyrrolidone is 1:0.05) are solid-phase mixed and sintered at 1250°C for 1 hour. After cooling to 30°C, methane is vapor-deposited on the surface of the high-temperature sintered product (the mass ratio of carbonaceous material to volume of methane is 100g:2.8L) and coated at 850°C for 1 hour. After cooling to 30°C, the product is sieved to obtain a median particle size D50 of 8.3μm.

[0066] Example 3

[0067] 2.5 kg of cellulose and 2.1 kg of hexamethylenetetramine were mixed and refluxed at 100°C for 2 hours, cooled to 30°C and filtered, and the filtered solid was dried at 95°C for 3 hours; the dried product was sintered at 400°C for 4 hours in a nitrogen atmosphere, cooled to 30°C, ground and sieved to D50 of 12±1 μm, washed with water, and dried at 100°C for 3 hours to obtain a carbonaceous material;

[0068] The carbonaceous material and a 5% glucose aqueous solution (the mass ratio of the carbonaceous material to the glucose aqueous solution is 100:150) are mixed and spray-dried, sintered at 1300°C for 1 h, cooled to 30°C, and acetylene is vapor-deposited on the surface of the product after high-temperature sintering (the mass ratio of the carbonaceous material to the volume of acetylene is 100g:3.2L), coated at 800°C for 0.8h, cooled to 30°C, and sieved to obtain a median particle size D50 of 11.8μm.

[0069] Example 4

[0070] 1 kgg of phenolic resin and 0.75 kg of triethylamine were mixed and refluxed at 100°C for 2 hours, cooled to 30°C and filtered, and the filtered solid was dried at 100°C for 2.5 hours; the dried product was sintered at 400°C for 4 hours in a nitrogen atmosphere, cooled to 30°C, ground and sieved to a D50 of 5±1 μm, acid-washed with a nitric acid solution with a pH value of 2, washed with water to neutrality, and dried at 105°C for 2.5 hours to obtain a carbonaceous material;

[0071] Ethylene was vapor deposited on the surface of the carbonaceous material (the ratio of the mass of the carbonaceous material to the volume of ethylene was 100 g:3 L), then vapor deposited at 1000°C for 1 hour. After cooling to 30°C, acetylene was vapor deposited again on the surface of the product after high-temperature sintering (the ratio of the mass of the carbonaceous material to the volume of ethylene was 100 g:3 L), sintered at 950°C for 1 hour, cooled to 30°C and sieved to obtain a median particle size D50 of 4.7 μm.

[0072] Example 5

[0073] The hard carbon material was prepared according to the method of Example 1, except that two high-temperature sinterings were combined into one high-temperature sintering, that is, glucose accounting for 10% by mass of the carbonaceous material was mixed with the carbonaceous material and subjected to one high-temperature sintering.

[0074] Comparative Example 1

[0075] The hard carbon material was prepared according to the method of Example 1, except that the reflux step was omitted and the apricot shell was directly sintered at a low temperature.

[0076] Comparative Example 2

[0077] A hard carbon material was prepared according to the method of Example 1, except that the washing steps of acid washing and water washing were omitted.

[0078] Comparative Example 3

[0079] The hard carbon material is prepared according to the method of Example 1, except that the two high-temperature sintering steps are omitted, and the carbonaceous material prepared in Example 1 is directly used as the hard carbon material.

[0080] The hard carbon material prepared in Example 1 was subjected to XRD detection to obtain an XRD spectrum, as shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the carbon coating layer on the surface of the hard carbon material is an amorphous carbon structure.

[0081] The hard carbon material obtained in Example 1 was subjected to scanning electron microscopy and the SEM image was obtained as follows: Figure 2 As shown. Figure 2 It can be seen that the hard carbon material obtained after coating in Example 1 has fewer surface defects.

[0082] The particle size of the hard carbon materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 was tested using Dandong Better Laser Particle Sizer BT-9300ST, and the results are listed in Comparison 1.

[0083] The specific surface areas of the hard carbon materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were measured using a Quantachrome NOVA4000e from the United States. The results are listed in Table 1.

[0084] The wavelength of CuKα ray was set to 0.15418 nm for XRD detection, and the d002 interlayer spacing was calculated according to Formula 1.

[0085] d002 = λ / (2sinθ) Formula 1;

[0086] Wherein, λ is the wavelength of X-ray (CuKam=0.15418); θ is the diffraction angle.

[0087] Table 1 Performance parameters of hard carbon materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3

[0088]

[0089] The hard carbon material, conductive carbon black and binder PVDF prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were mixed in pure water at a mass ratio of 96:1:3, homogenized, and the solid content was controlled at 48%, coated on a copper foil current collector, vacuum baked at 100 to 110°C for 6 hours, pressed and formed, and then punched to prepare a negative electrode sheet; a button half-cell was assembled in an argon-filled glove box, the counter electrode was a metal sodium sheet, the diaphragm used was PE, the molar concentration of NaPF6 in the electrolyte was 1 mol / L, and the solvent of the electrolyte was a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1. The button cell was charged and discharged, and the test process was 0.2C DC to 0V, 0.05C DC to 0V, 0V CV 50uA, 0.01C DC to 0V, 0V CV20uA, Rest 10min, 0.2C CC to 2V. The first reversible capacity and efficiency obtained by the test are listed in Table 2. The first charge and discharge curve of the button cell prepared by using the hard carbon material prepared in Example 1 as the negative electrode active material is shown in Table 2. Figure 3 shown.

[0090] The testing equipment for button batteries is the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.

[0091] Table 2 Electrochemical performance test data of negative electrode materials in Examples 1 to 5 and Comparative Examples 1 to 3

[0092]

[0093] Combined with Table 1 and Table 2 Figure 3 It can be seen that by using organic amine substances for reflux treatment and carbon coating on the surface of carbon materials, excellent performance negative electrode materials can be prepared, with the first reversible capacity of 301-322 mAh / g and the first efficiency of 87.7-91.8%.

[0094] In Comparative Example 1, without the treatment of organic amine substances, the interlayer spacing is significantly lower, the reversible capacity is only 285 mAh / g, and the first efficiency is 81.7%.

[0095] In Comparative Example 2, without purification treatment, there are more impurities, the capacity is only 278 mAh / g, and the first efficiency is 82.6%.

[0096] In Comparative Example 3, no coating treatment was performed, and there were many surface defects, and the reversible capacity and the first efficiency were significantly reduced, with a reversible capacity of 279 mAh / g and a first efficiency of 80.3%.

[0097] The coating amount of Example 5 is the same as that of Example 1, but the reversible capacity and the first efficiency of Example 5 are lower than those of Example 1. The reason may be that the excessive coating amount at one time leads to uneven coating and surface defects.

[0098] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A hard carbon material, comprising a carbonaceous material and a carbon coating layer on the surface of the carbonaceous material; The d002 interlayer spacing of the hard carbon material is 0.36-0.42 nm; the carbon coating layer is amorphous carbon; the thickness of the carbon coating layer is 30-1200 nm; The method for preparing the hard carbon material comprises the following steps: The first carbon source and the organic amine are mixed and then refluxed and low-temperature sintered in sequence to obtain a carbonaceous material; the reflux temperature is 75-120°C, and the reflux time is 2-5 hours; the low-temperature sintering temperature is 250-600°C; the first carbon source includes one or more of natural biomass materials, resin materials, asphalt and plant extracts; after the low-temperature sintering, the product after low-temperature sintering is ground and then washed; The carbonaceous material and the second carbon source are mixed and then sintered at high temperature to obtain the hard carbon material; the temperature of the high temperature sintering is 700-1500° C.; the number of times of the high temperature sintering is at least once.

2. The hard carbon material according to claim 1, characterized in that: The median particle size D50 of the hard carbon material is 2-18 μm.

3. The hard carbon material according to claim 1 or 2, characterized in that: The specific surface area of ​​the hard carbon material is 1 to 15 m 2 / g.

4. The method for preparing the hard carbon material according to any one of claims 1 to 3, comprising the following steps: The first carbon source and the organic amine are mixed and then refluxed and low-temperature sintered in sequence to obtain a carbonaceous material; the reflux temperature is 75-120°C, and the reflux time is 2-5 hours; the low-temperature sintering temperature is 250-600°C; the first carbon source includes one or more of natural biomass materials, resin materials, asphalt and plant extracts; after the low-temperature sintering, the product after low-temperature sintering is ground and then washed; The carbonaceous material and the second carbon source are mixed and then sintered at high temperature to obtain the hard carbon material; the temperature of the high temperature sintering is 700-1500° C.; the number of times of the high temperature sintering is at least once.

5. The preparation method according to claim 4, characterized in that: The low temperature sintering time is 1 to 6 hours.

6. The preparation method according to claim 4 or 5, characterized in that: The organic amine includes one or more of ethylenediamine, triethylamine, triethanolamine and hexamethylenetetramine; The mass ratio of the first carbon source to the organic amine is 1:0.5-1.

2.

7. The preparation method according to claim 4, characterized in that: The second carbon source includes a solid carbon source, a liquid carbon source or a gaseous carbon source; The mass ratio of the carbonaceous material to the second carbon source is 1:0.02-0.

2.

8. The preparation method according to claim 7, characterized in that: The solid carbon source includes one or more of polydopamine, polyvinyl pyrrolidone, polystyrene, asphalt, glucose and sucrose; The liquid carbon source is obtained by dissolving a solid carbon source in a solvent, and the solvent includes one or more of water, ethanol, toluene, ethyl acetate and n-heptane; The gaseous carbon source includes one or more of methane, ethane, ethylene, acetylene, propane, propylene, acetone, butane, butene, pentane and hexane.

9. Use of the hard carbon material according to any one of claims 1 to 3 or the hard carbon material prepared by the preparation method according to any one of claims 4 to 8 as a negative electrode material for a secondary battery.